Functional characterization of TRPM4 variants identified in sudden unexpected natural death. (December 2018) - Subbotina, Ekaterina; Williams, Nori; Sampson, Barbara A.; Tang, Yingying; Coetzee, William A.
Abstract: Background: The TRPM4 gene encodes the subunit of the Ca 2+ -activated nonselective cation channel, which is enriched in the specialized cardiac conduction system and Purkinje fibers. To date, several putative disease-causing variants in TRPM4 have been reported to be associated with cardiac arrhythmia and progressive conduction disease. Here, we report the functional effects of previously uncharacterized variants of uncertain significance (VUS) that we have found while performing a "genetic autopsy" in individuals who have suffered sudden unexpected death (SUD) in the New York City area. Methods and Results: We have identified thirteen uncommon missense VUS in TRPM4 by testing 95 targeted genes implicated in channelopathy and cardiomyopathy in 330 cases of SUD. In several cases there were co-existing VUS in one or more other genes that were tested. We selected four TRPM4 VUS (C20S, A380V, L595V and I1082S) for functional characterization, since these cases lacked detectable variants in other genes of our testing panel. Two of the cases were infants, one was a child and one an adult. RNA-seq data analysis showed that the longer TRPM4b splice variant is predominantly expressed in adult and fetal human heart. We therefore used site-directed mutagenesis to introduce these variants in a TRPM4b cDNA. HEK293 cells were transfected with the cDNAs and patch clamping was performed to assess the functional consequences of the TRPM4 mutants. The TRPM4 current was recorded in excised patches and was significantly reduced by each of the mutants. The total protein level of TRPM4-C20S was markedly decreased, whereas the A380V and L595V mutants exhibited decreased surface expression. The TRPM4-A380V current rapidly desensitized following patch excision. Conclusions: Each of the VUS tested caused a defect in TRPM4 channel function via distinctly different mechanisms, hence, it lays the foundation for further co-segregation family studies and animal studies of the TRPM4 variants.